Образование державы Ахеменидов по данным античных источников - Пьянков, И. В.
P’jankov, I. V.; The Formation of the Achaemenid Power according to the Data of Ancient Sources; engl. Résumé S. 335-336; Darstellung aufgrund antiker Autoren.